Analisis Hubungan Nilai Rebound Schmidt Hammer Dengan Nilai Uniaxial Compressive Strength (UCS) Pada Batupasir Formasi Balikpapan Dan Pulaubalang - Roberto Firson Pappang; Tommy Trides; Albertus Juvensius Pontus (Asosiasi Riset Ilmu Teknik Indonesia, 2024)
Uniaxial Compressive Strength is a test method to classify the strength and characterization of intact rock. Where it is important information in determining the strength and characteristics of a rock obtained by testing using the UCS tool. In this research, an alternative is made in determining the UCS value precisely and easily, namely by using the schmidt hammer test and compressive strength test. Therefore, this research aims to obtain the correlation value between the results of the compressive strength test and the schmidt hammer test on sandstone. Based on the results of observations and calculations that have been carried out, it can be concluded that the compressive strength value in the Balikpapan formation is lower than the compressive strength value in the Pulaubalang formation where the compressive strength value in the Balikpapan formation is 3.3 MPa-4.3 MPa, while the compressive strength value in the Pulaubalang formation is 4.3-5.57 MPa. The rebound number in the Balikpapan formation is lower than the rebound number in the Pulaubalang formation, where the rebound number in the Balikpapan formation is 16-17.8, while the rebound number in the Pulaubalang formation is 18-22.3. The correlation of the uniaxial compressive strength value with the rebound number of the schmidt hammer shows a positive linear correlation between the UCS value and the rebound number of the schmidt hammer, in this case it can be seen that when the uniaxial compressive strength value is higher, the rebound number of the schmidt hammer is also higher.